Impact of Operational Risk Toward the Efficiency of Banking - Evidence from Taiwans Banking Industry - Cheng, Cheng-Ping; Phung, Manh Trung; Hsiao, Chun-Lin; Shen, Da-Bai; Chen, Bih-Shiow (Asian Economic and Financial Review, 2018)
This study adopts a GARCH model to estimate the operational risk of Taiwan’s banking industry by the Top-Down method. Based on the approach of Battese and Coelli (1995) we estimate the Trans-log cost model and the inefficient model simultaneously by the Maximum likelihood method. Our empirical result shows that the operational risks have a significantly positive impact on cost inefficiency - that is, regardless of which methods we use for calculation, operational risk drives down economic efficiency. Comparing with the basic index method, the multi-factor model of the Top-Down method is better at analyzing the relationship of operational risk and efficiency.